Design and Evaluation of Tizanidine Buccal Mucoadhesive Patches - Gururaj S. Kulkarni, P.R.Sateesh Babu (Journal of Applied Pharmaceutical Science)
Mucoadhesive buccal dosage forms are becoming more popular and patient acceptable dosage forms. By this route advantages are many as the dose can be reduced, avoidance of first pass metabolism and liver toxicity, etc. The Tizanidine has first pass metabolism because of this the patient has to take more dose and two to three times in a day. To overcome this problem mucoadhesive patches of tizanidine are prepared and evaluated. Tizanidine is a non-selective, α-two adrenergic agonist receptor and used as muscle relaxant. The oral bioavailability of Tizanidine is 40%, because of first pass metabolism. The polymers used are polyvinyl alcohol and polyvinyl pyrolidine. FTIR and UV spectroscopic methods reveal that there is no interaction between tizanidine and polymers. The patches evaluated for various parameters and results are satisfied. In vitro release studies in phosphate buffer (pH, 6.6) exhibited drug release in the range of 71.68 to 97.27% in 90 min. The release of tizanidine from the patches followed first order, Higuchi’s model and mechanism diffusion rate limited. In vivo buccal absorption studies in rabbits showed 68.85% of drug releases from polyvinyl alcohol patch while it 67.52 to 88.31% within 90 min in human volunteers. Good correlation among in- vitro release and in- vivo studies observed.
Keywords: Tizanidine, Buccal patches, in vitro release, in vivo release, Evaluation.